2011
DOI: 10.5414/cp201509
|View full text |Cite
|
Sign up to set email alerts
|

Comparative pharmacokinetics and bioequivalence of two tablet formulations of 2 mg risperidone in healthy Thai male volunteers

Abstract: Background: Risperidone is an atypical antipsychotic drug with potent serotonin and moderate dopamine antagonistic properties. It possesses good bioavailability following oral administration. Risperidone is primarily converted by the cytochrome P450 2D6 (CYP2D6) and 3A4 (CYP3A4) enzymes to 9-hydroxyrisperidone, its active metabolite with equivalent potency to the parent compound. Objective: This study aimed to compare the pharmacokinetics and determine bioequivalence of two risperidone immediate release oral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…More recently, generic olanzapine and generic risperidone became available among European countries. Again, there appears to be no patient issues in practice (Araszkiewicz et al, 2008; Khorana et al, 2011; Wladysiuk et al, 2011; Correl and Carbon, 2012), although some authors are more cautious (Desmarais et al, 2011; Correl and Carbon, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…More recently, generic olanzapine and generic risperidone became available among European countries. Again, there appears to be no patient issues in practice (Araszkiewicz et al, 2008; Khorana et al, 2011; Wladysiuk et al, 2011; Correl and Carbon, 2012), although some authors are more cautious (Desmarais et al, 2011; Correl and Carbon, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The first atypical antipsychotic drug to become available as a generic in the UK was clozapine, with published studies, including those from the UK, showing no difference in outcomes between the originator and generics in practice, once initial the problems in the US had been resolved . More recently, generic olanzapine and generic risperidone have become available across Europe with again no apparent patient issues in practice , although some are more cautious .…”
Section: Introductionmentioning
confidence: 99%
“…Published studies have shown no difference in outcomes between the originator and generics once the problem with the first formulation in the USA had been resolved . More recently, generic olanzapine and generic risperidone became available with again no apparent patient issues in practice, although some authors are more cautious . However, it is recognised that schizophrenia and bipolar disorders are complex diseases to treat.…”
Section: Introductionmentioning
confidence: 99%